2019
DOI: 10.7554/elife.44187
|View full text |Cite
|
Sign up to set email alerts
|

An acquired scaffolding function of the DNAJ-PKAc fusion contributes to oncogenic signaling in fibrolamellar carcinoma

Abstract: Fibrolamellar carcinoma (FLC) is a rare liver cancer. FLCs uniquely produce DNAJ-PKAc, a chimeric enzyme consisting of a chaperonin-binding domain fused to the Cα subunit of protein kinase A. Biochemical analyses of clinical samples reveal that a unique property of this fusion enzyme is the ability to recruit heat shock protein 70 (Hsp70). This cellular chaperonin is frequently up-regulated in cancers. Gene-editing of mouse hepatocytes generated disease-relevant AML12DNAJ-PKAc cell lines. Further analyses indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 74 publications
5
109
0
Order By: Relevance
“…Despite little differences conferred to the structure and activity of the kinase by the fusion of the J-domain, in vivo studies have shed light on the signaling changes induced by the chimeric fusion. Recently, Scott and co-workers suggested that the J-domain is able to recruit Hsp70, stabilizing the chimeric fusion protein 16 . Together with the higher expression levels due to the DNAJB1 gene 7 , the enhanced stability of the enzyme in complex with Hsp70 may explain the dominant expression in FL-HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Despite little differences conferred to the structure and activity of the kinase by the fusion of the J-domain, in vivo studies have shed light on the signaling changes induced by the chimeric fusion. Recently, Scott and co-workers suggested that the J-domain is able to recruit Hsp70, stabilizing the chimeric fusion protein 16 . Together with the higher expression levels due to the DNAJB1 gene 7 , the enhanced stability of the enzyme in complex with Hsp70 may explain the dominant expression in FL-HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…A unique feature of FL-HCC is instead the production of a chimeric enzyme able to recruit heat shock protein 70 (Hsp70), thus triggering oncogenic signalling. Chimeric DNAJ-PKAc consists of a chaperonin-binding domain (DNAJ) fused to the Cα subunit of protein kinase A (PKA), an important effector of cAMP signalling [11].…”
Section: Introductionmentioning
confidence: 99%
“…6D). The second model is the AML12 cell line that has undergone CRISPR/Cas9 gene editing, resulting in a heterozygous deletion analogous to the endogenous event in humans, leading to the formation of the Dnajb1-Prkaca fusion (Dinh et al, 2019;Turnham et al, 2019). When we examined the expression of the genes of interest in AML12 cells expressing Dnajb1-Prkaca, we found that Car12 and Slc16a14, as well as Rps6ka2 and Vcan, are significantly elevated compared to wild-type (WT) controls ( Fig.…”
Section: High-confidence Candidate Oncogenes In Flcmentioning
confidence: 99%